Factors associated with parental grief reaction following pediatric acquired brain injury. Issue 1 (2nd January 2021) - Yehene, Einat; Brezner, Amichai; Ben-Valid, Shani; Golan, Sapir; Bar-Nadav, Ofri; Landa, Janna
ABSTRACT: The present study investigated factors associated with parental grief reaction (PGR) following pediatric acquired brain injury (ABI), and compared PGR to the one exhibited following child death. Fifty-seven parents of 51 children (aged 3–18) whose ABI occurred 1–14 years before participation, completed the multi-scale Two-Track Bereavement Questionnaire; a socio-demographic questionnaire; and a scale assessing perceived behavioural changes in the child. Results from regression analysis indicated that time since injury had no impact on parents' grief other than having an adverse impact on their overall coping and functioning; A higher amount of weekly caring hours predicted only a greater traumatic perception of the loss; Older children's ages but mostly greater parental-perceived behavioural changes, predicted greater PGR on most scales. PGR was compared with the pre-existing data of bereaved parents who completed the same grief questionnaire. Although grief response patterns and intensity were similar in both groups, significant differences were found on scales assessing the continuing bond with the child: relational active grief, close and positive relationship, and conflictual relationship. Our findings indicate that parental grief is multi-dimensional following pediatric ABI and illuminate the interplay between elements characterizing parents' nonfinite vs. finite loss experience.